2005
DOI: 10.1007/978-3-540-31956-6_53
|View full text |Cite
|
Sign up to set email alerts
|

On the Security of Cluster-Based Communication Protocols for Wireless Sensor Networks

Abstract: Wireless sensor networks are ad hoc networks comprised mainly of small sensor nodes with limited resources, and are rapidly emerging as a technology for large-scale, lowcost, automated sensing and monitoring of different environments of interest. Cluster-based communication has been proposed for these networks for various reasons such as scalability and energy efficiency. In this paper, we investigate the problem of adding security to clusterbased communication protocols for homogeneous wireless sensor network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 8 publications
0
77
0
3
Order By: Relevance
“…SecLEACH [7] is an improvement of SLEACH [6]. Hence, SecLEACH shows how a random key pre-distribution can be used for secure communication in cluster-based protocols.…”
Section: Related Workmentioning
confidence: 99%
“…SecLEACH [7] is an improvement of SLEACH [6]. Hence, SecLEACH shows how a random key pre-distribution can be used for secure communication in cluster-based protocols.…”
Section: Related Workmentioning
confidence: 99%
“…SLEACH [20] proposed some additions to LEACH so that it can improve protection for the network. It is suggested that each node has to have two symmetric keys: a pairwise key shared with the BS and the last key chain held by the BS.…”
Section: Sleachmentioning
confidence: 99%
“…Several clustering protocols for wireless sensor are presented in the literature [7,8,9,10,11,12,13]. While some of these protocols show a new method of partitioning the network with a view to minimize the energy consumed by the sensors [7,8,9], some others handle the security aspect [10,11,12,13] during the clustering in order to secure communications in the network.…”
Section: Introductionmentioning
confidence: 99%
“…While some of these protocols show a new method of partitioning the network with a view to minimize the energy consumed by the sensors [7,8,9], some others handle the security aspect [10,11,12,13] during the clustering in order to secure communications in the network. However, since the WSN infrastructure is not previously defined and that the WSN is facing significant hardware constraints, it is important to always look for new mechanisms to improve existing ones.…”
Section: Introductionmentioning
confidence: 99%